The Dermatological Effects and Occupational Impacts of Personal Protective Equipment on a Large Sample of Healthcare Workers During the COVID-19 Pandemic - Santoro, Paolo Emilio; Borrelli, Ivan; Gualano, Maria Rosaria; Proietti, Ilaria; Skroza, Nevena; Rossi, Maria Francesca; Amantea, Carlotta; Daniele, Alessandra; Ricciardi, Walter; Potenza, Concetta; Moscato, Umberto (Frontiers in Public Health, 2022)
Introduction Working during the Sars-CoV-2 pandemic healthcare workers (HCWs) had to wear Personal Protective Equipment (PPEs) for extended periods of time, leading to an increase in dermatological reactions. The study evaluates the prevalence of adverse skin reactions to PPEs among Italian healthcare workers during the COVID-19 pandemic, and aims to determine whether prolonged PPEs usage poses a significant occupational health risk, by measuring the loss of work days and the eligibility of workers that requested health surveillance due to dermatological PPEs reactions. Materials and Methods An online ad hoc questionnaire was administered to a sample of Italian HCWs. Questions verted on sociodemographic characteristics, PPEs usage, and occupational well-being. Descriptive analyses and logistic regressions were performed to explore possible associations between variables. Results Two types of PPEs, Gloves and Masks, were tested. The sample included 1,223 interviewed HCWs, 1,184 gave their consent for participation. A total of 90 medical surveillance visits were requested due to PPEs related dermatological issues: in 30 cases were recognized limitations in working duties and in one case the worker was deemed not fit to keep working. Furthermore, 25 workers had a loss of occupational days due to dermatological issues. A statistically significant correlation was observed with being a nurse or midwife (OR = 1.91, IC = 1.38–2.63, p < 0.001), and being female (OR = 2.04, IC = 1.49–2.78, p < 0.001), which acted as risk factors. Discussion The enhanced protection measures put in place during the COVID-19 pandemic, highlight the importance of occupational dermatology. This study could contribute to assess the issue, aiming to develop better prevention strategies in the workplace in order to improve well-being of HCWs and reduce the impact of dermatological adverse reactions to PPEs.